METHODS AND PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF PROFESSIONAL CULTURE AMONG CADETS OF PRE-CONSCRIPTION MILITARY TRAINING (Scientific journal of the Fergana State University, 2024)
This article provides an overview and analysis of the concept of professional culture in the context of pre-conscription military training. She examines the essence and main aspects of professional culture, its importance for the training of future military personnel. The paper highlights various points of view on this concept, presented by experts in the field of civil and military science and practice. The aspects of the introduction of professional culture concepts into the process of pre-conscription military training and their impact on the formation of the qualities of future military personnel are analyzed. As a result of such a study, it is planned to draw conclusions about the importance of professional culture in the process of preparing young people for service in the Armed Forces.